Relationship of morphometric and productive variables on reproductive parameters in Romosinuano and Costeño con cuernos cows - Herrera Perez, Nathalia del Carmen; Canabal Vidal, Mario Alberto; Abuabara Pérez, Yesid José; Ossa Saraz, Gustavo Alfonso; Garcés Blanquiceth, Jorge Luis; Fernández Niño, Juan Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective. To establish the effect of morphometric and productive measures on reproductive parameters: a number of calvings and calving interval in Romosinuano (ROMO) and Costeño con Cuernos (CCC) females under agro-climatic conditions of the Colombian humid Caribbean. Materials and methods. The following morphometric measurements were taken: ischial width (ADI), hip width (ADC), sacral height (ADS), withers height (ADLC), as well as live weight, first calving weight (PPP), last calving weight (PUP), body condition (CC), and reproductive parameters such as the number of calvings and calving intervals (IEP). Differences between morphometric and reproductive parameters by breed were established by analysis of variance. Relationships between morphometric and reproductive variables were analyzed through canonical correlations. Results.  The analysis of variance showed statistically significant differences (p<0.05) between morphometric measurements and live weight by breed. The study of canonical correlations allowed the establishment ADI, ADLC, PPP, and PUP as the canonical variables significantly essential and have a significant relationship with the number of calvings.  Conclusion. Weight and PUP are the variables with the greatest effect on the reproductive parameters evaluated in Romosinuano and Costeño con Cuerno cows.